2009
DOI: 10.1074/jbc.c900007200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of α-Dystroglycan Laminin Binding in Epithelium-derived Cancers Is Caused by Silencing of LARGE

Abstract: The interaction between epithelial cells and the extracellular matrix is crucial for tissue architecture and function and is compromised during cancer progression. Dystroglycan is a membrane receptor that mediates interactions between cells and basement membranes in various epithelia. In many epithelium-derived cancers, ␤-dystroglycan is expressed, but ␣-dystroglycan is not detected. Here we report that ␣-dystroglycan is correctly expressed and trafficked to the cell membrane but lacks laminin binding as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 32 publications
9
103
1
Order By: Relevance
“…Hence, ␣-DG-dependent migration controlled by HNK-1ST might predominate in HNK-1-negative melanomas. The unique glycan structure expressed on ␣-DG has been shown to have a close relationship to tumor-related phenotypes such as invasiveness (32,33). Previous studies reported that the IIH6 mAb-reactive glycan of ␣-DG had a suppressive effect on tumor invasion in cases of breast, prostate, and lung carcinoma (32,33), although we obtained the opposite results using melanoma cells (Figs.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Hence, ␣-DG-dependent migration controlled by HNK-1ST might predominate in HNK-1-negative melanomas. The unique glycan structure expressed on ␣-DG has been shown to have a close relationship to tumor-related phenotypes such as invasiveness (32,33). Previous studies reported that the IIH6 mAb-reactive glycan of ␣-DG had a suppressive effect on tumor invasion in cases of breast, prostate, and lung carcinoma (32,33), although we obtained the opposite results using melanoma cells (Figs.…”
Section: Discussionmentioning
confidence: 52%
“…It has been demonstrated that ␣-DG, especially the glycan attached to it, is involved in tumor invasiveness in various cancer types such as breast, prostate, and lung carcinomas (32,33). Because HNK-1ST associates with the modification of glycans, up-regulation of HNK-1ST expression might affect the glycosylation in cells.…”
Section: Specific Induction Of Hnk-1st Expression and Alternatementioning
confidence: 99%
See 1 more Smart Citation
“…This situation is exemplified in studies using cancer cells. It has been reported that several malignant cancer cell types lose the laminin-binding glycan of ␣-DG due to epigenetic down-regulation of LARGE or defects in the LARGE-binding protein ␤3GnT1, raising the possibility of defects in post-phosphoryl modification of ␣-DG in those cells (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated antimigratory activity of laminin-binding glycans attached to ␣-DG. While we were preparing our article, a report appeared showing that downregulation of LARGE resulted in higher migration of carcinoma cells (29).…”
Section: Expression Of ␤3gnt1 Directs the Synthesis Of Laminin-bindinmentioning
confidence: 99%